Government and Banking in Western Nigeria : A Case Study in Economic Policy - Brown, Charles V. (Ibadan : Published for the Nigerian Institute of Social and Economic Research [by] Oxford University Press, 1964)
This monograph consists of a case study in implementation of economic policy. The policy that is examined is the policy of the Western Nigeria Government in aiding indigenous banks.
"Taken from a larger study ... being prepared as a thesis for the University of London."
Bibliography: p. 141.
osc 17/7/17
Loans
Keywords: Banks and Banking